Preparation of Nano-Co3O4 by Direct Thermal Decomposition of Cobalt(II) Nitrate Hexahydrate for Electrochemical Water Oxidation - Ahmed Qasem, Mohammed A.; Aziz, Md. Abdul; Hakeem, Abbas Saeed; Onaizi, Sagheer A. (Current Nanoscience, 2018)
Background: Nano-Co3O4 has been used in various technological areas and applications such as electrochemical sensors and electrochemical water splitting. Even though many efforts have been expended to prepare nano-Co3O4, the development of novel methods to prepare Co3O4 using simple processes and at low cost remain a topic of interest. Besides, it could be economic and useful if the synthesized nanoparticle could be applied as efficient electrocatalyst upon its immobilization on a cheap base electrode material by very simple method for various practical applications including renewable energy. Method: We prepared nano-Co3O4 by a direct thermal decomposition of an inexpensive, simple and widely available cobalt inorganic precursor, such as Co(NO3)2·6H2O without any type of prereaction or processing. The nano-Co3O4 was immobilized on filter-paper-derived carbon electrode by drop-drying method for applying as electrode materials toward water electrooxidation. Results: The X-ray diffraction, field emission scanning electron microscopy, and transmission electron microscopy analysis confirmed the formation of short nanorods of single-phase Co3O4 upon thermal decomposition of Co(NO3)2·6H2O at 520°C. The electrocatalytic properties of the nano- Co3O4 were evaluated after immobilizing it on a cheap carbon electrode derived from normal filter paper. The modified electrode showed good electrocatalytic properties toward water oxidation in an alkaline solution. Conclusion: In conclusion, we developed a very simple, straight-forward and economic method for preparation of nano-Co3O4 and immobilized it on very cheap carbon electrode for evaluating its electrocatalytic properties. Due to the high electrocatalytic properties, the prepared nano-Co3O4 could potentially play an important role in various practical fields.
Keywords: nano-Co3O4